Turizmo plėtros sąlygos Rytų Aukštaitijos regiono savivaldybėse - Gražulis, Vladimiras; Narkūnienė, Ramutė (Socialiniai tyrimai, 2017)
The authors of the article discuss tourism development conditions in the municipalities in Eastern Aukštaitija region. Scientific problem: tourism development trends at local, municipality, level have not been sufficiently studied in Lithuania, tourism has been developing without a clear, long-term development strategy and a consistent tourism development programme in districts. Scientific literature review, survey results, document, SWOT analysis are provided in the paper.